2014
DOI: 10.2108/zs130181
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Upstream Migration of the Amphidromous Teleost, AyuPlecoglossus altivelis

Abstract: Changes in mRNA levels of prolactin (PRL) during the upstream migration were examined in fry of the amphidromous fish, ayu Plecoglossus altivelis. Quantification of mRNA has been done with real-time PCR and expressed as whole body or pituitary contents depending the body size of fry. PRL mRNA levels of ayu caught in seawater of the coastal area remained low during early spring. Prior to the start of the upstream migration, the fish caught in the coastal area in mid spring showed increased levels of PRL mRNA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Wang et al [53] reported that Aquaporin I performs an important regulatory function in Coilia nasus under conditions of salinity stress. Prolactin has also been reported to have a regulatory function when freshwater fish swim into seawater [54]. In this study, the prolactin receptors were upregulated to assist with the anti-stress response of C. nasus.…”
Section: Response Regulation Under Salinity and Cold Effectmentioning
confidence: 67%
“…Wang et al [53] reported that Aquaporin I performs an important regulatory function in Coilia nasus under conditions of salinity stress. Prolactin has also been reported to have a regulatory function when freshwater fish swim into seawater [54]. In this study, the prolactin receptors were upregulated to assist with the anti-stress response of C. nasus.…”
Section: Response Regulation Under Salinity and Cold Effectmentioning
confidence: 67%
“…The survival time seemed to be related to their native environmental salinity, suggesting that, upon hyposmotic challenge, the reliance on pituitary control of osmoregulation was less critical in FW species relative to their congeners that were naturally subject to variations in salinity. In anadromous fishes, such as salmonids and ayu ( Plecoglossus altivelis ), PRL seems to be involved in their migration from FW to SW and vice versa (Onuma et al, 2003; Taniyama et al, 1999; Yada et al, 2010; Yada et al, 2014), but of limited importance in FW osmoregulation (Makino et al, 2007; Manzon, 2002). Two PRL isoforms have been reported in tilapias (Specker et al, 1985), chum salmon ( Oncorhynchus keta ; Yasuda et al, 1986), common carp ( Cyprinus carpio ; Yasuda et al, 1987) and Japanese eel ( Anguilla japonica ; Suzuki et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that ayu undergoes changes in hormonal levels (prolactin and thyroxine) in accordance with the onset of upstream migration and after riverine residency (Tsukamoto & Uchida, 1992; Yada et al, 2014). This physiological change can be tracked by the quantification of mRNA (Yada et al, 2014). These findings imply that specific detection of eRNA derived from mRNA regarding hormone synthesis might be able to differentiate groups with different behaviors (i.e., sea residents, upstream migrants, and river residents).…”
Section: Discussionmentioning
confidence: 92%
“…Compared to eDNA, eRNA has the potential to significantly improve spatial and temporal resolution in biological monitoring due to its rapid turnover and enhanced diagnostics of population and community characteristics (Yates et al, 2021). Previous research has shown that ayu undergoes changes in hormonal levels (prolactin and thyroxine) in accordance with the onset of upstream migration and after riverine residency (Tsukamoto & Uchida, 1992;Yada et al, 2014). This physiological change can be tracked by the quantification of mRNA (Yada et al, 2014).…”
Section: Discussionmentioning
confidence: 98%